2024
DOI: 10.1088/1361-648x/ad2389
|View full text |Cite
|
Sign up to set email alerts
|

Tunable electronic properties and optoelectronic characteristics of MoGe2N4/SiC van der Waals heterostructure

Ning Yang,
Hui Li,
Guogang Liu
et al.

Abstract: The assembly of van der Waals (vdw) heterostructure with easily regulated electronic properties provides a new way for the expansion of two-dimentional (2D) materials and promotes the development of optoelectronics, sensors, switching devices and other fields. In this work, a systematic investigation of the electronic properties of MoGe2N4/SiC heterostructures using density functional theory (DFT) has been conducted, along with the modulation of electronic properties by vertical strain and the potential appli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The combination of MoGe 2 N 4 and other 2D materials has also been investigated extensively to uncover novel phenomena, giving rise to the development of vdW-based heterostructures towards multifunctional applications. Many heterostructures combining MoGe 2 N 4 with other 2D materials have been proposed and discovered, such as BP/MoGe 2 N 4 , 38 graphene/MoGe 2 N 4 , 39 SiC/MoGe 2 N 4 40 and so forth. 41 For instance, Nguyen et al 38 constructed the BP/MoGe 2 N 4 heterostructure and predicted that its formation would lead to an enhancement in the material's absorption coefficient in both the visible and ultraviolet light regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The combination of MoGe 2 N 4 and other 2D materials has also been investigated extensively to uncover novel phenomena, giving rise to the development of vdW-based heterostructures towards multifunctional applications. Many heterostructures combining MoGe 2 N 4 with other 2D materials have been proposed and discovered, such as BP/MoGe 2 N 4 , 38 graphene/MoGe 2 N 4 , 39 SiC/MoGe 2 N 4 40 and so forth. 41 For instance, Nguyen et al 38 constructed the BP/MoGe 2 N 4 heterostructure and predicted that its formation would lead to an enhancement in the material's absorption coefficient in both the visible and ultraviolet light regions.…”
Section: Introductionmentioning
confidence: 99%
“…41 For instance, Nguyen et al 38 constructed the BP/MoGe 2 N 4 heterostructure and predicted that its formation would lead to an enhancement in the material's absorption coefficient in both the visible and ultraviolet light regions. Yang et al 40 demonstrated that the combination in the SiC/MoGe 2 N 4 heterostructure effectively enhances the electronic and optical properties of the constituent SiC and MoGe 2 N 4 monolayers. All these findings suggest that an MoGe 2 N 4 monolayer can be considered as a promising material for the design of novel heterostructures, characterized by structural stability and the emergence of novel phenomena.…”
Section: Introductionmentioning
confidence: 99%